Implementasi Arsitektur Microservice pada Back End Sistem Informasi Atlantas berbasis Website - Seviro Bima Sakti, Calvin; Hermawan, Indra (LPPM STT Terpadu Nurul Fikri, 2020)
The number of traffic violations that occurred in the Depok area from 2017 to 2019 has fluctuated, from 2017 as many as 33,600 cases, 2018 as many as 52,100 cases and 2019 as many as 42971 cases. In each year an increase in violations occurs and the ability of applications to distribute data will decrease. This happened to the Traffic Unit of the Depok Metro Police, with the increasing number of handling data on accidents and data on violations that occurred in Depok City, of course, it must be balanced with an increase in the system as an online reporting medium. From the above explanation, it can be concluded that to solve this process, it is necessary to have a new architecture, namely the microservice. Microservice allows the development of software functions to be broken down into small, focused service parts, making the service have resource capabilities that can be precisely managed and dividing application functionality into small and interconnected services into a single business application process. This architecture integrates data between units, distributes data related to cases of traffic violations or accidents that occur in real time by local police officers, and provides information on traffic violations and specific accidents.